Clinical Assessment and Emergency Management of Transient Ischemic Attack - Alanazi, Faleh Turki Hammad; Hussain Ali Jubran Shafei; Omar Mahmoud Abduljawad; Nooh Thawab Almotiri; Abdullah Hussain Ghazi Alghazi; Ibrahim Mohammed Ibrahim Otudi; Ayoub Ali Mohamed Aldarbi; Faisal Saud Almutaiti; Eman Mohammed Almadan; Anfal Abdulrazaq Alabdulwahed; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Transient ischemic attack (TIA) is a neurological emergency characterized by temporary focal ischemia without permanent infarction. It serves as a critical warning for impending stroke, with the highest risk occurring within 48 hours post-event. Aim: To review the clinical assessment, emergency management, and preventive strategies for TIA, emphasizing early recognition and intervention to reduce stroke risk. Methods: This review synthesizes current evidence and guidelines on TIA evaluation and management, including neuroimaging, vascular and cardiac assessment, laboratory investigations, and risk stratification using the ABCD² score. It also examines therapeutic approaches such as antiplatelet therapy, anticoagulation, and lifestyle modification. Results: Early and comprehensive evaluation significantly reduces stroke risk. MRI with diffusion-weighted imaging is preferred for diagnosis, while vascular imaging and cardiac monitoring identify treatable sources. Dual antiplatelet therapy for 21–30 days post-TIA, followed by monotherapy, is effective in non-cardioembolic cases. Carotid endarterectomy benefits patients with high-grade stenosis, and anticoagulation is indicated for cardioembolic TIA. Integrated strategies combining pharmacologic therapy and lifestyle changes can reduce recurrent stroke risk by up to 80%. Conclusion: TIA requires urgent, multidisciplinary management. Rapid diagnosis, risk stratification, and targeted interventions are essential to prevent subsequent ischemic events. Evidence supports a multifaceted approach involving imaging, pharmacologic therapy, and risk factor modification to optimize outcomes.